Emotional experiences of the children of alcoholic fathers - Akbaş, S.; Böke, Ö.; Karabekiroğlu, K. (Journal of Dependence, 2008)
Objective: This study aimed to investigate the negative life events experienced by children living with alcoholic fathers, the influence of their parents’ attitudes, and the attitudes they develop as a result of these influences. Method: A retrospective review of the files of children of alcoholic fathers who were treated for alcohol dependence and underwent psychiatric evaluations in child psychiatry was conducted. Psychiatric interviews with the children in the files assessed their experiences during the period when their parents used alcohol and the impact of their fathers’ alcoholism. Findings: The files of thirty-three children were evaluated. The children reported 93.9% family problems, 81.8% negative life events, 63.6% witnessing or experiencing domestic violence, 51.5% parental separation, and 60.6% exposure to their fathers’ negative behavior. Children developed behavioral and emotional responses such as sadness (81.8%), fear (69.7%), a desire to stay away from their fathers (36.4%), anxiety about their mothers (24.2%), clinging to their mothers (21.2%), an inability to be alone (18.2%), and an inability to sleep alone (15.2%). Conclusion: The study found that children were affected by parental separation, the domestic violence they encountered, and their fathers’ negative attitudes and behaviors during periods of alcohol use. Children were found to experience sadness and fear in the face of negative life events experienced by their fathers during periods of alcohol use, and, in parallel, they desired to stay away from their fathers, experienced anxiety about their mothers, and developed behaviors such as clinging to their mothers.